Pannell Products strike, c. 1970
1971 1960-2000 "Pannell Products strike, c. 1970" [EP0016], c. 1970 Strike for union recognition and fair wages by women members of the General and Municipal Workers Union at a clothing firm, Pannell Products, c1970.